Diagnosis strategy design method based on ant colony algorithm. Issue 1 (April 2021) - Yun, Lin; Lu, Han
Abstract: Diagnosis strategy design is an important step in testability design. In order to be close to the reality, the optimization design of diagnosis strategy is carried out under the condition of unreliable test. Firstly, the changes caused by unreliable test conditions are analyzed, and test cost and error cost are established as optimization objectives. Then the mathematical model of the problem is established. Ant colony algorithm is used to solve the problem, and a new heuristic evaluation function is established. the objective function is redefined. Finally, the effectiveness of the proposed method is verified by an example and compared with other algorithms.